RANCANG BANGUN ALAT PEMANTAU PASANG SURUT AIR LAUT MELALUI JARINGAN INTERNET UNTUK KAWASAN TELUK KENDARI - Bardan Bulaka; Hendro Hendro (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
English version of the abstract be written here. Has created a system monitor water levels that can be used to monitor the phenomenon of the tide in the Gulf of Kendari by using the Internet network. Hardware or device used consisted of an ultrasonic sensor is used to measure the distance of the surface of the water, the microcontroller Arduino Uno that serves to process data readings from ultrasonic sensors and WiFi module ESP8266 ESP-01 which serves to connect the microcontroller to the Internet network (data server) , The hardware of the system is tested on the water surface inside a container penampukan water, where the water level inside the container is assumed as the sea level. Tests conducted to determine the feasibility of such a device before it is applied in the area of ​​Teluk Kendari. Data from the measurement of the water level can be accessed by anyone with a browser using either a computer (PC), laptop, or smartphone connected to the Internet network. Applications used to monitor water levels through the Internet is ThingSpeak contained on the website www.thingspeak.com. Keywords: Monitors, Sensors, Microcontroller, Internet, ThingSpeak.